Ebola: Responding to its Outbreak in West Africa - Shuman, Jill (MD Conference Express, 2014)
According to the US Centers for Disease Control and Prevention, the 2014 Ebola outbreak in West Africa is the largest Ebola outbreak in history and the first to be classified as an epidemic. This article reviews the clinical characteristics of patients infected with Ebola, as well as reviews the global response in tracking and managing the outbreak and provided an overview of potential therapeutic options.